Using Flow 3D Simulation, Multiple Nonlinear Regression Approach, and Artificial Neural Network Approach Approaches to Study the Behavior of Vertical Drop Structures - Shaikhli Hasan Al; Mohammed Sarah Hashim; Al-Khafaji Zainab (Civil and Environmental Engineering)
The “Vertical Drop” is a hydraulic structure widely utilized in irrigation and wastewater collection systems to equalize height differences between channel slopes and the natural terrain. Previous studies of vertical drops primarily focused on experimental investigations of their hydraulic properties. This study numerically analyzes the hydraulic features of vertical drops with inverse aprons using FLOW3D software and the finite volume method. The volume of fluid (VOF) technique was employed to simulate the free surface. Key flow parameters, such as downstream depth, pool depth, and energy loss, were calculated and validated against experimental data. Various turbulence models and grid configurations were assessed. The numerical results, achieved with a grid size of 20,000 nodes, a downstream channel length of 2 meters, the standard k-ε turbulence model, and a standard wall function, exhibited excellent agreement with theoretical equations. Downstream depth, pool depth, and energy loss closely matched experimental findings. Additionally, numerical impact velocities were compared with empirical equations across different scenarios, demonstrating minimal deviation. These findings confirm that the velocity characteristics of the falling jet can be reliably estimated numerically.